Selective deletion of Pten in theca-interstitial cells leads to androgen excess and ovarian dysfunction in mice. (15th March 2017) - Lan, Zi-Jian; Krause, M.S.; Redding, S.D.; Li, X.; Wu, G.Z.; Zhou, H.X.; Bohler, H.C.; Ko, C.; Cooney, A.J.; Zhou, Junmei; Lei, Z.M.
Abstract: Theca cell-selective Pten mutation ( tPtenMT ) in mice resulted in increases in PDK1 and Akt phosphorylation, indicating an over-activation of PI3K signaling in the ovaries. These mice displayed elevated androgen levels, ovary enlargement, antral follicle accumulation, early fertility loss and increased expression of Lhcgr and genes that are crucial to androgenesis. These abnormalities were partially reversed by treatments of PI3K or Akt inhibitor. LH actions in Pten deficient theca cells were potentiated. The phosphorylation of Foxo1 was increased, while the binding of Foxo1 to forkhead response elements in the Lhcgr promoter was reduced in tPtenMT theca cells, implying a mechanism by which PI3K/Akt-induced upregulation of Lhcgr in theca cells might be mediated by reducing the inhibitory effect of Foxo1 on the Lhcgr promoter. The phenotype of tPtenMT females is reminiscent of human PCOS and suggests that dysregulated PI3K cascade in theca cells may be involved in certain types of PCOS pathogenesis. Highlights: Selective theca mutant mice for Pten ( tPtenMT ). tPtenMT mice exhibit androgen excess, ovulation dysfunction and early loss of female fertility. The phenotype resembles human polycystic ovary syndrome (PCOS).